Seminoma in a Man with Russell-Silver Syndrome Presenting with Testicular Torsion. (29th February 2016) - Funada, Satoshi; Ikeuchi, Ryosuke; Yoshida, Toru; Segawa, Takehiko
Abstract : Russell-Silver syndrome (RSS) is a type of primordial dwarfism. Only one case of testicular cancer in RSS has been reported, the pathology of which was nonseminoma. Here, we report a case of seminoma in a 36-year-old man who was diagnosed with RSS at birth. The seminoma was diagnosed when the patient presented with testicular torsion. This is the first report of testicular seminoma in an RSS patient in the literature. We also discussed the correlation between seminoma and RSS.